The Increasing of South Korean Investment in Vietnam - Silvi Cory (Frequency of International Relations (FETRIAN), 2022)
South Korea as one of the countries that has actively invested in various countries. In recent years South Korean investment has shown a very significant increase in Vietnam. When compared to other countries, especially in the Asian region, Vietnam is not a country that rich in natural resources as many know that country that has many natural resources will get special key in investment. However, South Korea has different movement that its significant effort to build its investment in Vietnam. This paper aims to explains the factors that make South Korea significantly increase its investment in Vietnam. This research is a qualitative research using descriptive analysis method. This study finds that the stability of domestic political, social, cultural conditions, economic growth, human resources, stability in labor wages and various number of Vietnam's FTA cooperation with various countries have become factors that attract South Korea to invest in Vietnam.